Influence of landscape retention capacity upon flood processes in Jičínka river basin - Pavlík, František; Dumbrovský, Miroslav (Mendel University Press, 2014)
This paper describes the retention capacity of the river basin and its course during a flash flood. Retention capacity of the river basin was measured of balancing of precipitation fallen in the river basin and discharges in the final profile. For determine the retention characteristics of the river basin was used method, which balances precipitation and runoff in the time step. The method is based on the theory of separation of components of runoff and also used the analogy with transformation of the flood discharge through a reservoir.

This paper describes the retention capacity of the river basin and its course during a flash flood. Retention capacity of the river basin was measured of balancing of precipitation fallen in the river basin and discharges in the final profile. For determine the retention characteristics of the river basin was used method, which balances precipitation and runoff in the time step. The method is based on the theory of separation of components of runoff and also used the analogy with transformation of the flood discharge through a reservoir.
Influence of landscape retention capacity upon flood processes in Jičínka river basin
Keywords: landscape; retention; flood flows; river basin; landscape; retention; flood flows; river basin